Source of Hyalesthes obsoletus Signoret planthopper (Hemiptera: Cixiidae) in southern France and potential effects of landscape. Issue 2 (11th September 2017) - Hossard, L.; Guimier, S.; Vinatier, F.; Barbier, J.M.; Delmotte, S.; Fontaine, M.; Rivoal, J.B.
Abstract: Cixiid planthoppers are considered of major economic importance, as they can transmit phytoplasmas responsible for many plant diseases. While thorougly studied in vineyards, the epidemiology of stolbur phytoplasma, transmitted by Hyalesthes obsoletus Signoret, was rarely investigated on minor crops as lavender, where it leads to 'yellow decline' disease and large economic losses. The objective of this paper is to understand the effect of the local landscape characteristics on the presence and density of H. obsoletus in the 'Plateau de Valensole', southern France. Potential host plants of H. obsoletus were surveyed in three contrasted zones (in terms of crops and disease intensity), by uprooting plants and capturing adults in emergence traps. The localization and potential movements of H. obsoletus from the host plants towards lavandin (infertile hybrid of lavender) were determined using yellow sticky traps. Clary sage plants were found as major hosts of H. obsoletus . Flying insects were also caught in fields of lavandin, although emergence traps and plant uprooting did not confirm this crop as a winter host, i.e., as a reservoir for the insect. Based on one zone, we showed that attractiveness may depend on crop (clary sage or lavandin) and on its age, as well as on the distance to the supposed source field. These results suggest that clary sage could be an important host of H. obsoletus, whose density largely varies between zones. Genetic studies would be required to confirm the role of clary sage in the dissemination of yellow decline of lavandin.